MULTIPLE INTELEGEN DALAM PEMBELAJARAN PAI TRANSPORMATIF DI SDIT AL BINA PURWAKARTA JAWA BARAT - Metty Suhaemi; Manpan Drajat (CBJIS : Cross-Border Journal of Islamic Studies, 2021)
The background of the problem is SDIT Al Bina Purwakarta, West Java, has a PAI Transformative Education Program to educate students. according to Plural intelligence. The purpose of this research is to get an overview of Transformative Multiple Intelligence Education. The methodology used is qualitative to get an overview of the principal respondents, teachers, administration and students as well as parents of students. student. Data analysis techniques can be obtained by way of interview. observation and documentation . Primary data can be obtained from the principal, Administration. Teachers, students and parents. secondary data can be obtained from books and documentation. The results of the research of SDIT Al Bina Purwakarta students, West Java, improve Transormative PAI education in Multiple Intelligence through curriculum reform, planning and implementation as well as evaluation.